Properties of graphene composite fiber seamless knitted fabric and its application in boxing training - Liu, Tianyue (Frontiers in Materials, 2023)
Considering that in boxing training, physical injuries are often caused due to wrong movements and other reasons, and many sports protective clothing would use new materials to reduce the impact on the body during boxing training. This paper aims to design a boxing suit based on a graphene composite fiber seamless knitted fabric to reduce the injuries caused by boxing trainers during training. For graphene composite fiber seamless knitted fabrics, the veil, inner yarn and weave structure of the fabrics were discussed, and the composition of 9 kinds of fabrics was determined by orthogonal matrix. For the performance analysis of fabrics, this paper also proposed a comprehensive evaluation of the wearability of fabrics based on the entropy weight TOPSIS method. Finally, the boxing protective clothing was designed according to the composition with the best performance. The experimental results in this paper showed that the veil of sample No. 7 is 70D/48F graphene nylon, the inner yarn is 30D graphene spandex/70D graphene nylon covered yarn, and the fabric with the weave structure of 1+3 false rib has the best comprehensive performance and the highest relative proximity, reaching 0.862. The actual wearing test proved that the comfort of the impact-resistant boxing suit is slightly better than that of the ordinary boxing suit, but the clothing designed in this paper has a good impact-resistance effect. Therefore, on the whole, the boxing suit of graphene composite fiber seamless knitted fabric has a good protective effect and can be used in boxing training.